2010
DOI: 10.1123/ijsnem.20.2.104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Carbohydrate-Electrolyte Fluids on Cycling Performance and Maximal Voluntary Contraction

Abstract: The purpose of this study was to compare the effects of a carbohydrate-electrolyte plus caffeine, carnitine, taurine, and B vitamins solution (CE+) and a carbohydrate-electrolyte-only solution (CE) vs. a placebo solution (PLA) on cycling performance and maximal voluntary contraction (MVC). In a randomized, double-blind, crossover, repeated-measures design, 14 male cyclists (M ± SD age 27 ± 6 yr, VO 2max 60.4 ± 6.8 ml · kg -1 · min -1 ) cycled for 120 min submaximally (alternating 61% ± 5% and 75% ± 5% VO 2max … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 46 publications
(64 reference statements)
3
23
1
Order By: Relevance
“…Doherty and Smith (2005) reported that caffeine reduces rating of perceived exertion (RPE) during exercise which explained approximately 30% of increased performance in response to caffeine ingestion. Supporting this result are recent studies (Cureton et al, 2007;Ganio et al, 2010) showing caffeine-mediated reductions in RPE during 2 h of submaximal cycling as well as improved performance during a subsequent 15 min time trial. However, existing literature suggests that RPE is not attenuated at the end of exhaustive exercise, as caffeine seems not to alter performance at intensities approaching maximum (Dodd, Brooks, & Powers, 1991;Powers, Byrd, Tulley, & Callender, 1983).…”
Section: Introductionsupporting
confidence: 79%
“…Doherty and Smith (2005) reported that caffeine reduces rating of perceived exertion (RPE) during exercise which explained approximately 30% of increased performance in response to caffeine ingestion. Supporting this result are recent studies (Cureton et al, 2007;Ganio et al, 2010) showing caffeine-mediated reductions in RPE during 2 h of submaximal cycling as well as improved performance during a subsequent 15 min time trial. However, existing literature suggests that RPE is not attenuated at the end of exhaustive exercise, as caffeine seems not to alter performance at intensities approaching maximum (Dodd, Brooks, & Powers, 1991;Powers, Byrd, Tulley, & Callender, 1983).…”
Section: Introductionsupporting
confidence: 79%
“…80,202,229,230 Competitive athletes can benefit from carbohydrate-electrolyte beverages before activity. 82,116,222,224 Physically active people eating a balanced diet with adequate calories and fluids need not add ingredients to water to maintain hydration status. Beverages that appeal to individual taste preferences may encourage individuals to drink more fluids.…”
Section: Beverage Additivesmentioning
confidence: 99%
“…116,118,119,121 Small amounts of caffeine in a rehydration beverage should not cause harm to the physically active postexercise.…”
Section: Beverage Additivesmentioning
confidence: 99%
“…The following methods and results were collected as part of a larger double-blind, randomized, crossover study which compared two carbohydrate-electrolyte drinks versus placebo (i.e., the water solution used in the present study); this larger study focused on prolonged cycling performance and knee extensor maximal voluntary contraction (Ganio et al 2009). Only the methods and results directly relating to the placebo condition are reported here.…”
Section: Methodsmentioning
confidence: 99%